2012
DOI: 10.1364/oe.20.011277
|View full text |Cite
|
Sign up to set email alerts
|

THz near-field Faraday imaging in hybrid metamaterials

Abstract: Abstract:We report on direct measurements of the magnetic near-field of metamaterial split ring resonators at terahertz frequencies using a magnetic field sensitive material. Specifically, planar split ring resonators are fabricated on a single magneto-optically active terbium gallium garnet crystal. Normally incident terahertz radiation couples to the resonator inducing a magnetic dipole oscillating perpendicular to the crystal surface. Faraday rotation of the polarisation of a near-infrared probe beam direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…This fine resolution is especially helpful in studying phase transitions close to the critical temperature since the areal averaging in traditional far-field measurement techniques can hinder the data interpretation in systems with complex phases. s-SNOM is able to distinguish different phases in the coexistence region and directly accesses fundamental properties of the materials, enabling direct mapping of the IR electronic structure at extreme subwavelength scales [32][33][34]. The unique sensitivity of s-SNOM facilitates the strain engineering presented in this study.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This fine resolution is especially helpful in studying phase transitions close to the critical temperature since the areal averaging in traditional far-field measurement techniques can hinder the data interpretation in systems with complex phases. s-SNOM is able to distinguish different phases in the coexistence region and directly accesses fundamental properties of the materials, enabling direct mapping of the IR electronic structure at extreme subwavelength scales [32][33][34]. The unique sensitivity of s-SNOM facilitates the strain engineering presented in this study.…”
Section: Resultsmentioning
confidence: 97%
“…In order to probe the electronic properties at the nano-scale, scattering scanning near-field optical microscopy (s-SNOM) is used to image the IR properties of the samples at single frequencies (10-11 m) or collect spectra at specific locations with a broadband light source. The infrared near-field apparatus has ~10 nm spatial resolution (~/1000) -far beyond the light diffraction limit (~/2) -ensuring optical imaging and spectroscopic identification without integrating the information from mixed phases [17,[22][23][24][25][26][27][28][29][30][31][32][33][34]. This fine resolution is especially helpful in studying phase transitions close to the critical temperature since the areal averaging in traditional far-field measurement techniques can hinder the data interpretation in systems with complex phases.…”
Section: Resultsmentioning
confidence: 99%
“…41,42 Direct measurement of magnetic fields in the near-field region has also been demonstrated. 43 In this article, we use photoconductive switches imprinted on 1-µm-thin low-temperaturegrown GaAs micro-probe tips 17 to measure all the individual components of the complex electric near-field in three dimensions near a gold rod resonant at THz frequencies. It has already been shown that these tips show negligible invasiveness to resonant structures.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several methods have been used to measure the near-field of objects. [6] These include THz apertureless near-field scanning optical microscopy [7][8][9], which uses a small metal tip to sample the THz light in a small, sub-wavelength sized volume, as well as THz photoconductive sampling using antennas [10][11][12][13], electro-optic detection with a tightly focused probe beam [14][15][16] and, most recently, magnetooptic sampling of a metamaterial [17]. In near-field measurements, it is important to suppress unwanted background THz light coming from the incident THz electric field or from light scattered off objects elsewhere.…”
Section: Introductionmentioning
confidence: 99%